51Cr-Bleomycin in the Diagnosis of Ocular Melanoma - Liniecki, J.; Pertynski, T.; Krawczykowa, Z.; Stepien, J.; Durski, K. (Nuklearmedizin - NuclearMedicine, 1983)
51Cr-bleomycin was administered to 18 patients suspected of having an ocular melanoma with varying degree of development. The diagnosis was verified prior to surgical removal of the eye-ball by fluorescent angiography and computerized axial tomography. In operated patients histological diagnosis was also available. Scintigraphy after 51Cr-bleomycin administration appeared to be an effective diagnostic measure: sensitivity and specificity reached 90 and 87%, respectively. It is concluded that the method is useful in the preoperative diagnosis of ocular melanoma.